Proportion of the processed food and ultra-processed food (UPF) consumption and its associated factors among adults attending general clinics in Hospital Universiti Sains Malaysia - Husain, Mohd Hilmi Mat (2024)
Nutritional-related diseases have emerged as a major public health concern, contributing to premature mortality and significantly impacting the increasing prevalence of obesity, noncommunicable diseases, and cardiovascular disease. Processed food and ultraprocessed food are usually formulated industrially. Ultra-processed food is characterised by its energy- density, reduced nutritious ingredients, and hyperpalatable taste, and it has strong links with adverse health outcomes. This study aimed to determine the proportion of the processed food and ultra-processed food consumption among adults attending general clinics at Hospital USM and its associated factors. This is a cross-sectional study that collected primary data from adults who went to general clinics at Hospital USM using a sociodemographic and Malay-validated food frequency questionnaire based on NOVA classification. We assessed the ultra-processed food diversity score by summing the different ultra-processed foods consumed within a week, which facilitated the classification of low and high consumption. Multiple logistic regression was used to predict factors associated with an increased level of ultra-processed food consumption among adults attending general clinics at Hospital USM. The majority of the respondents were female (64.6%), Malay (90.8%), single (62.2%), and belonged to the B40 household income group (68.1%). The most common ultra-processed foods consumed were packaged bread, yellow noodles, cocoa drinks, and flavoured milk drinks. The proportion of respondents who had a high ultra-processed food diversity score was 54%, indicating more than half had consumed ultra-processed food seven times per week. Screen time (AOR 2.148, 95% CI: 1.181–3.906, p-value = 0.012), having received financial aid (AOR 2.436, 95% CI: 1.267–4.684, p-value = 0.008), and being unemployed (AOR 2.436, 95% CI: 1.267–4.684, p-value = 0.023) were significantly associated with high consumption of ultra-processed among adults aged 18–39 years old attending general clinics Hospital USM. In conclusion, most adults attending general clinics in Hospital USM consume ultra-processed food regularly. The factors identified in this study may suggest areas of action for policymakers to explore ways to limit ultra-processed food consumption to achieve better health outcomes.